Percepción de la calidad de atención de los clientes de una empresa del rubro de productos de limpieza, Trujillo 2022 - Gonzales Rodríguez, Deysi Lasteni (2023)
The objective of this study is to determine the degree of quality of service perceived by _x000D_ consumers of a cleaning supplies company, Trujillo 2022. This work is quantitative and has _x000D_ a descriptive design; 192 consumers served during the research period, in November 2022, _x000D_ formed the systematic random sample. By means of the survey technique, a duly validated _x000D_ and reliable questionnaire was used, and a descriptive analysis was made of the quality of _x000D_ service in general, as well as in each of its dimensions, such as waiting time to be attended, _x000D_ user treatment, staff efficiency and accessibility to service hours. The most significant _x000D_ finding is that 45% of consumers believe that the quality of customer service is good, 49%, _x000D_ 46% and 52% believe that the level of waiting time to be attended to, user treatment and _x000D_ accessibility to service hours is good, and only 39% believe that the level of staff efficiency _x000D_ is average; finally, it is decided that the degree of customer service quality recognized by _x000D_ consumers of cleaning products companies is good, with 45% of consumers in Trujillo in _x000D_ 2022 believing this to be the case